Prognostic role of epidermal growth factor receptors’ expression in patients with i-ii stage of non-small cell lung cancer - A.P. Kolesnik; A.I. Shevchenko; V.A. Tumansky; A.V. Evseev; M.A. Shishkin (Patologìâ)
Introduction: